Consumption practices and perception of ready-to-eat food among university students and employees in Kuala Lumpur, Malaysia - R. S., Basurra; Robin, Tunung; C., Kavita; Alan, Ribka; M., Chandrika; Anyi, Ubong (Rynnye Lyan Resources, 2021)
The purpose of the study was to examine the consumption practices and perception of ready-to-eat food among university students and employees in Kuala Lumpur, Malaysia. Through random sampling, a total of ninety-three respondents participated by answering questionnaires. The results showed that majority of the respondents (52%) consumed RTE food two to four times a week, and most of them (44%) consumed RTE food during lunch. The biggest motivator for the respondents to purchase RTE food was convenience (46%). It could be highlighted that majority of the respondents felt that fast-food restaurants to be very safe (11.8%), and that street foods to be very risky (34.4%). Most of the respondents were very worried about human spread diseases (such as Hepatitis B) and human spread bacteria (such as E. coli) when buying food (43%). When buying RTE food, consumers were most concerned about the cleanliness of the store they were buying their food from (66.7%). The present study indicated that university students and employees showed food safety awareness and concerns especially regarding RTE food. This study could benefit food marketers, and also public health organizations in their efforts to develop more effective education and dissemination of information to the public.